Human agency, self-efficacy, and academic achievement: Analysis of “Asia’s educational miracle” in Confucian relational cultures - Kim, Uichol; Tubbs, Naomi (Educação: Teoria e Prática, 2025)
This article examines the factors behind the “Asian Educational Miracle,” focusing on Confucian relational cultures and studies from South Korea. Unlike the Western individualistic view, which emphasizes innate ability, the East Asian perspective highlights the self and relatedness to others. The article describes self-development and the socialization of culture in children to explain academic achievement. Bandura’s Social Cognitive Theory, based on human agency and self-efficacy, provides the scientific foundation for understanding culture and performance. Bandura criticizes traditional theories that focus on biology, innate abilities, and mechanical cognitive processing, arguing that they ignore intention and forethought as precursors to action. Academic success occurs through personal, proxy, and collective control. Advances in genetics and neurobiology challenge traditional assumptions and support Bandura’s theory. Studies in South Korea demonstrate the role of self-efficacy and social support from parents, friends, and teachers in academic achievement. These findings highlight the importance of human agency, self-efficacy, and social support, as well as the impact of personal, proxy, and collective agency on academic success and moral disengagement, which may partly explain school violence and delinquency.